The Dynamics of Values among Future Sport Pedagogues in the Last Decade - Malinauskas, Romualdas (Pedagogika, 2016)
The problem of this research can be defined by the following research question: what is the dynamics of values held by future sport pedagogues in the last decade? The study in 2004 documented number characteristics of values among future sport pedagogues. The study conducted in 2014 aimed to answer the question of whether the changing social environment and educational reform in the last decade is related to the future sports pedagogues’ values change. It was presumed that students in 2004 and students in 2014 have different values. Three surveys used were the Rokeach Value Survey for identification of the most important personal values, Leontiev Life Meaning Orientations Test for the evaluation of values pertaining to the meaning of life (defined as ideas about life goals, processes, results and control of life circumstances), Sniras Moral Value Survey for identification of the most important moral values. Not the same first year students were investigated twice: the first time in the year 2004 (N = 168) and the second time in the year 2014 (N = 163). The research findings revealed that ‘material well-being’ (financially secure lifestyle) and ‘public recognition’ (respect and authority) were the most important values among future sport pedagogues in the year 2004 compared to them in year 2014. ‘Clear life goals’ was the value pertaining to the meaning of life that was most significant to future sport pedagogues in 2014 compared to them in 2004. Forgiveness (not to diminish, not to revenge) was a significantly less important value for the first-year future sport pedagogues in 2014 than it was for them in year 2004.